Bioenergetic Shifts during Transitions between Stem Cell States (2013 Grover Conference Series). (1st September 2014) - Zhang, Lianghui; Marsboom, Glenn; Glick, Danielle; Zhang, Yanmin; Toth, Peter T.; Jones, Nicole; Malik, Asrar B.; Rehman, Jalees
Abstract : Two defining characteristics of stem cells are their multilineage differentiation potential (multipotency or pluripotency) and their capacity for self‐renewal. Growth factors are well‐established regulators of stem cell differentiation and self renewal, but less is known about the influence of the metabolic state on stem cell function. Recent studies investigating cellular metabolism during the differentiation of adult stem cells, human embryonic stem cells (ESCs), and induced pluripotent stem cells have demonstrated that activation of specific metabolic pathways depends on the type of stem cells as well as the lineage cells are differentiating into and that these metabolic pathways can influence the differentiation process. However, some common patterns have emerged, suggesting that undifferentiated stem cells primarily rely on glycolysis to meet energy demands. Our own data indicate that undifferentiated ESCs not only exhibit a low mitochondrial membrane potential but also express high levels of the mitochondrial uncoupling protein 2 and of glutamine metabolism regulators when compared with differentiated cells. More importantly, interventions that target stem cell metabolism are able to either prevent or enhance differentiation. These findings suggest that the metabolic state of stem cells is not just a marker of their differentiation status but also plays an active role in regulating stem cell function. Regulatory metabolic pathways in stem cells may thus serve as important checkpoints that can be modulated to direct the regenerative capacity of stem cells.